The Effect of Self-Management and Digital Readiness on Teacher Professionalism: Evidence from Junior High Schools in Manado, Indonesia - Lestari Paat; Harol R. Lumapow; Elni J. Usoh; Romi J. Mongdong (JR Education, 2026)
In the era of digital transformation, teacher professionalism has become a critical determinant of educational quality, yet its relationship with self-regulatory capacity and digital preparedness remains underexplored in developing-country contexts. Empirical evidence from Indonesian schools indicates that teachers' levels of self-management and digital readiness remain varied and suboptimal, potentially undermining effective teaching performance in technology-integrated learning environments. This study aimed to examine the partial and simultaneous effects of self-management and digital readiness on teacher professionalism among junior high school teachers in Paal Dua District, Manado City, Indonesia. A quantitative explanatory research design was employed. Data were collected via a validated Likert-scale questionnaire administered to 85 respondents, selected using the Slovin formula (e = 0.05) from a population of 108 teachers across eight schools. Multiple linear regression analysis was conducted using IBM SPSS Statistics. Self-management had a positive and significant effect on teacher professionalism (β = 0.434, t = 4.911, p < 0.001), while digital readiness also exerted a positive and significant influence (β = 0.413, t = 4.681, p < 0.001). Self-management emerged as the more dominant predictor. Simultaneously, both variables significantly predicted teacher professionalism (F = 23.115, p < 0.001), explaining 36.1% of its variance (R² = 0.361). The integration of self-management capabilities and digital readiness constitutes a key determinant of teacher professionalism in digitally transforming educational settings. These findings provide an empirical basis for school administrators and education policymakers to design targeted teacher professional development programs that simultaneously strengthen self-management competencies and digital readiness.